You've got mail - Ephron, Delia (Warner Bros, 1998)
Three little words. Three rapturous words that Joe Fox (Tom Hanks) and Kathleen kelly (Meg Ryan) long to hear: You've Got Mail. As frothy as a triple latte and as refreshing as a springtime walk, You've Got Mail delivers all the wit, charm and warmth you'd expect from a reunion of the stars and directors (Nora Ephron) of sleepless in Seattle. Greg Kinnear, Parker Posey, Jean Stapleton and more talented co-stars add perfect support to this valentine to modern - to- modern romance in which suerstore book chain magnate Hanks and cozy children's bookshop owner Ryan play anonymous e-mail cyberpals who fall head-over-laptops in love, unaware that they are combative business rivals. "Tom Hanks and Meg Ryan are magic," Joel Siegel of ABC-TV's Good Morning America proclaims. And it's a magic to be shared when You've Got Mail.